Rheology properties of Dodecyl-Î²-D-maltoside stabilised mineral oil-in-water emulsions - Niraula, B.; King, T.C.; Misran, M. (2003)
Rheology properties of dodecyl-Î²-D-maltoside stabilized mineral oil-water (o-w) emulsions were studied. A strain controlled Rheometer was used for this purpose. Shear sweep was carried out to observe the Î·(Î³) behavior, whereas oscillatory sweep was carried out to observe the Gâ²(Ï) and Gâ³(Ï) behaviors. All rheology properties examined in this work including Î·(Î³), Ï(Î³) Gâ²(Ï) and Gâ³(Ï) were found to be exhibiting typical non-linear power law dependence. Î·-Î³ profiles suggested that these sample do not exhibit zero shear rate limiting viscosity and terminal relaxation time, that Î· of these samples decays exponentially as a function of both the Î³ and surfactant concentration with a characteristic power law index, exponent of which decreases with surfactant concentration. Plot of Ï(Î³) suggested that Ï was not a linear function of Î³ at low-shear rate domain, but an exponentially growing function with a certain power exponent. At zero shear rate the stress response was not zero, implying that samples under investigation were shear thinning non-ideal plastic-like materials, with characteristic ÏY response. Much like Î· which increased with surfactant concentration at any given shear rate, both ÏY and Î·0 increased with surfactant concentration. Analysis of Ï dependence of dynamic moduli suggested that at a very low Ï domain below 1Hz, the Gâ² response of these samples was dominant over Gâ³ response, and that the Gâ² response was a more or less a linear function of Ï, suggesting that these samples are solid-like materials. On the other hand, at higher Ï domain beyond 1Hz, the Gâ³ response of these samples was dominant over Gâ² response, but neither Gâ²(Ï) was found to be a linear function of Ï 2, nor Gâ³(Ï) a linear function of Ï, implying that the samples under examination were neither liquid-like nor solid-like materials. These in turn suggested that these samples cannot be characterized by Maxwell model type fluid flow behavior. Both the dynamic moduli decreased with surfactant concentration. Cole-Cole plot representing Gâ³ response against Gâ² strongly deviated from the usual semi-circle characteristic of Maxwell model type fluid flow behavior, further confirming that these samples do not exhibit Maxwell model type fluid flow behavior. While tanÎ´ grew linearly as a function of Ï, it was comparably high in both the low and high Ï domain, implying that these o-w emulsion exhibited more liquid-like viscous behavior than solid-like elastic behavior. The tanÎ´ was both Ï and surfactant concentration dependent. While it decreased with both the surfactant concentration and Ï at low-frequency domain, it was almost independent of both the surfactant concentration and Ï.